Prevalence and predictors of antibiotic use among children visiting the Emergency Department in a tertiary hospital in Malaysia - Tham, Daniel Wai Je; Abubakar, Usman; Tangiisuran, Balamurugan (Springer, 2020)
Abstract: Inappropriate use of antibiotics in human and animal is one of the causes of antimicrobial resistance. This study evaluates the prevalence and predictors of antibiotic use among pediatric patients visiting the Emergency Department (ED) in Malaysia. A retrospective cross-sectional study was conducted in the ED of a tertiary hospital. Data of children aged 2 to 11 years who visited the ED from January–May 2015 were extracted from the patient’s assessment forms. A total of 549 children were included in the analysis (median age 5 years) of which 54.3% were boys. Upper respiratory tract infections (URTI) were the most common diagnosis. Antibiotic was prescribed in 43.5% of the children.Children who visited the ED during the weekend (OR, 1.65; 95% confidence interval (CI) 1.13–2.40, P=0.009), those diagnosed with URTI (OR 3.81; 95% CI, 2.45–5.93, P<0.001) and those with a longer duration of fever (OR, 1.31; 95% CI, 1.15–1.48, P<0.001) were more likely to have an antibiotic prescription. Conclusions: Antibiotic was prescribed in more than one-third of children who visited the ED and antibiotic use was associated with visits during the weekend, URTI, and duration of fever. Antimicrobial stewardship program is recommended in the pediatric ED to improve appropriate use of antibiotics.